PERJUANGAN KARAKTER CINTA TANAH AIR DARI SEORANG PAHLAWAN REVOLUSI PIERRE TENDEAN - Restu Amaliyah Putri (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
Character values ​​are the basic values ​​of behavior that become the reference for the values ​​of interaction between humans (when character is lost then everything is lost). Universally, various characters are formulated as values ​​of living together based on the pillars: responsibility, peace, honesty, freedom, respect, cooperation, humility, happiness, simplicity, compassion, tolerance, and unity Endang Ekowarni. Thus the character values ​​that can be used as guidelines or benchmarks can be seen from the figure of the Indonesian revolution, Pierre Tendean. Pierre Tendean has a character of love for the country, enthusiasm and never give up in him. as well as his discipline from a young age taught by his parents, especially from his father. From the explanation above, the author is interested in raising the title of the research article is the struggle of the character of love for the homeland from a revolutionary hero, Pierre Tendean.This research is a qualitative research using the historical method or the historical method with a literature study approach. This research aims to analyze a character struggle for the love of the country from the revolutionary hero Peirre Tendean in his book about Pierre Tendean's biography. Keywords: Pierre Tendean, Value of Love the Motherland Character